Targeting the latent human cytomegalovirus reservoir for T-cell-mediated killing with virus-specific nanobodies - Timo W. M. De Groof (Nature Portfolio, 2021)
Human cytomegalovirus (HCMV) can evade immune responses in latent reservoirs, which is a specific problem during transplantation. Here the authors develop a bivalent nanobody that is specific for US28, a viral receptor required by latent HCMV, and show it can partially reactivate the virus and make it susceptible to killing by T cells.